Adjuvant Therapy: Melanoma. (19th December 2011) - Davar, Diwakar; Tarhini, Ahmad; Kirkwood, John M.
Abstract : With an incidence that is increasing at 2–5% per year, cutaneous melanoma is an international scourge that disproportionately targets young individuals. Despite much research, the treatment of advanced disease is still quite challenging. Immunotherapy with high-dose interferon- α 2b or interleukin-2 benefits a select group of patients in the adjuvant and metastatic settings, respectively, with significant attendant toxicity. Advances in the biology of malignant melanoma and the role of immunomodulatory therapy have produced advances that have stunned the field. In this paper, we review the data for the use of interferon- α 2b in various dosing ranges, vaccine therapy, and the role of radiotherapy in the adjuvant setting for malignant melanoma. Recent trials in the metastatic setting using anticytoxic T-lymphocyte antigen-4 (anti-CTLA-4) monoclonal antibody therapy and BRAF inhibitor therapy have demonstrated clear benefit with prolongation of survival. Trials investigating combinations of these novel agents with existing immunomodulators are at present underway.